Application of Mudharabah Contracts on Products Fundraising at Bank Riau Kepri Capem Duri - Siska Derly (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2019)
The type of research that will be used in this thesis is a qualitative method. Data collection techniques used are observation, interviews, and documentation. The analysis techniques used are data reduction, data presentation, and drawing conclusionsAfter the author conducted the research, the author can conclude that in the application of the mudharabah contract to the savings product, it is applied to the iB Sinar Amanah Riau (SINAR) savings product. Applying mudharabah contracts to current accounts, Bank Riau Kepri Capem Duri has an iB current account mudharabah product, where this product applies the mudharabah principle as a contract in its products. Applying the mudharabah contract to deposit products, Bank Riau Kepri Capem Duri has a deposit product called iB Deposito Mudharabah Bank Riau Kepri. Of all the fundraising products offered by Bank Riau Kepri Capem Duri, each product has a different profit-sharing ratio.